The relationship between intimate partner abuse and somatic complaints and illnesses - Karakuła, Hanna; Łukasik, Paulina; Juchnowicz, Dariusz; Pitucha, Alina; Lecyk, Anna (Current Problems of Psychiatry, 2011)
Intimate partner abuse causes not only mental disorders and short-term physical problems. Chronic stress and fear have long-term health consequences concerning various organs and systems.Aim of the presented work was to review available literature on the prevalence of domestic violence in general practice, with a focus on patients’ somatic complaints and co-occurring illnesses.Conclusions: 1. Despite raising public awareness of domestic violence, the full scale of the phenomenon is difficult to estimate. 2. Women experiencing abuse are more likely to seek for medical help, having more somatic complaints and an increased risk of developing somatic illnesses. 3. Due to the high frequency of domestic violence, its serious consequences for both mental and physical health, there is a need of undertaking further research in this area and developing programs aimed at sensitizing health care workers to its early warning signs.